2004
DOI: 10.1080/01926230490431466
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema and Metalloelastase Expression in Mouse Lung Induced by Cigarette Smoke

Abstract: Cigarette smoke (CS) causes pulmonary emphysema in humans and elastin degradation plays a key role in its pathogenesis. Previous studies on CS-exposed animals have been equivocal and have not clearly demonstrated the progression of the disease. In this study, morphometry was used to assess lung modifications to alveolar septa, airspaces, elastic and collagen fibers, and alveolar macrophages. Male (n = 40) C57/BL6 mice were exposed 3 times/day, whole body, to CS from three cigarettes for 10, 20, 30, or 60 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 34 publications
5
71
1
3
Order By: Relevance
“…Inflammatory lesions in mouse lung exposed to cigarette smoke is also associated with a significant increase of alveolar macrophages expressing MMP-12 (Valença et al, 2004).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 98%
“…Inflammatory lesions in mouse lung exposed to cigarette smoke is also associated with a significant increase of alveolar macrophages expressing MMP-12 (Valença et al, 2004).…”
Section: Spinal Cord Injury (Sci)mentioning
confidence: 98%
“…Indeed, MMP-12 generates elastin-derived peptides and experiments performed in modified Boyden chambers have shown that these elastin-derived peptides are chemotactic for monocytes (26). In a more recent study, it was reported that inflammatory lesions in the lungs of mice contained significantly more MMP-12 in macrophages at 10, 20, and 30 days of cigarette smoke exposure than in control mice exposed to 60 days (27). These results suggest that elastin degradation took place during the development of pulmonary change in mice exposed to cigarette smoke and activation of elastin-specific MMPs may be a determining factor for susceptibility to emphysema (27).…”
Section: Role Of Mmp In the Development Of Airway Inflammation In Chrmentioning
confidence: 98%
“…This constant and unidirectional flow carries body smells, excrement smells, and gases expelled by the animals themselves, preventing them from contaminating the internal environment of the chamber. Constant air renewal into the chamber is an advantage compared to chambers working with controlled pressure (Hemenway and Stedman 1981, Lopes 2004, Pereira 2004, those which do not have unidirectional flow, in which the chamber air outlet is near to the entrance (Bung et al1984, Vincent and Guénette 1997, Schenkel et al 2009), and inhalation boxes (Valença et al 2004, Komyia et al 2006, Bradley et al 2007, Takemoto et al 2008, Ito and Ito 2011.…”
Section: Developed Inhalation Chamber Structurementioning
confidence: 99%
“…Furthermore, apparatus containing an inhalation box (Valença et al 2004, Komyia et al 2006, Bradley et al 2007, Takemoto et al 2008, Ito and Ito 2011 and those that do not present a unidirectional flow of insufflated material (Hemenway and Stedman 1981, Bung et al 1984, Vincent and Guénette 1997, Lopes 2004, Pereira 2004, Schenkel et al 2009) are prone to the accumulation and deposition of such test materials. This may result in the administration of more than the required dose due to both accumulation inside the chamber and deposition on the animals' bodies.…”
Section: Saturation Timementioning
confidence: 99%
See 1 more Smart Citation